2020
DOI: 10.5219/1338
|View full text |Cite
|
Sign up to set email alerts
|

Mastitis pathogens and somatic cell count in ewes milk

Abstract: The aim of this study was to determine the occurrence of pathogens in selected group of ewes and the relationship between somatic cell count (SCC) and the presence of pathogens. The experiment was carried out on a dairy farm, where predominantly breed was a Tsigai. Sampling was carried out in monthly intervals as part of the milk recording test day from February to July 2019. A total of 303 ewes were included in the survey, during the milk recording test day. The ewes with SCC ≥1000 × 103 cells.mL-1 were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
1
7
0
3
Order By: Relevance
“…However, it also notes that while MALDI-TOF-MS has revolutionized speed and precision of microbial identification for clinical isolates, in contrast few performance studies have been published so far focusing on suitability for particularly industrial applications. In addition to CoNS (Tvarožková et al, 2020), the species S. aureus (Zigo et al 2011;Tančin et al 2017;Holko et al 2018) is often identified in milk and dairy products, similarly to our study where in bryndza its presence was confirmed by both methods.…”
Section: Discussionsupporting
confidence: 89%
“…However, it also notes that while MALDI-TOF-MS has revolutionized speed and precision of microbial identification for clinical isolates, in contrast few performance studies have been published so far focusing on suitability for particularly industrial applications. In addition to CoNS (Tvarožková et al, 2020), the species S. aureus (Zigo et al 2011;Tančin et al 2017;Holko et al 2018) is often identified in milk and dairy products, similarly to our study where in bryndza its presence was confirmed by both methods.…”
Section: Discussionsupporting
confidence: 89%
“…Many of them can be classified as functional foods in different geographical and social localities. However, European Union regulations oblige producers to obtain milk only form healthy animals in order to increase consumers safety, what however may limit milk production and consumption ( 1 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The overall prevalence of the bacteriological positive milk samples was 36.73% from separate udder halves of ewes. Vasileiou et al (2018) detected 26% occurrence of subclinical mastitis and other study found 36.1% prevalence of subclinical mastitis (Tvarozkova et al 2020). The negative bacteriological samples formed 60.20% of the total tested samples.…”
Section: Resultsmentioning
confidence: 72%
“…The milk samples at half udder level were divided based on somatic cell count to five SCC groups: SCC1 < 200 000 cells/ml (45 milk samples); 200 000 ≤ SCC2 < 400 000 cells/ml (10 milk samples); 400 000 ≤ SCC3 < 600 000 cells/ml (six milk samples); 600 000 ≤ SCC4 < 1 000 000 cells/ml (six milk samples); SCC5 ≥ 1 000 000 cells/ml (31 milk Czech Journal of Animal Science, 66, 2021 ( 08 (Tvarozkova et al 2020). In the study of Ergun et al (2009), the occurrence of S. aureus was observed in 3.1% of milk samples without clinical signs.…”
Section: Determination and Categories Of The Sccmentioning
confidence: 99%